A severe case of acute respiratory distress syndrome (ARDS) in a primigravida recently diagnosed with acute myeloid leukemia (AML) - Joshi, Sonia; Gandee, Zachary; Baron, Rebecca Marlene; Hou, Peter Chuanyi (Journal of Emergency and Critical Care Medicine; Vol 2 (November 2018): Journal of Emergency and Critical Care Medicine, 2018)
The incidence of leukemia during gestation ranges from 1 in 75,000 to 1 in 100,000. We report a rare case of acute respiratory distress syndrome (ARDS) in a 30-year-old second trimester primigravida diagnosed with acute myeloid leukemia (AML) upon hospital admission (Figure 1A,B).